Quarter Life Crisis Card Game Design Based on The Purpose Venn Diagram and IPE Ciputra Concept - Santoso, Alexandra Ruth; Agustin, Hanna (VCD: Journal of Visual Communication Design, 2023)
As individuals transition towards emerging adulthood, the younger generation often experiences what is commonly referred to as a quarter-life crisis. Anxiety in choosing a profession and the future is a problem that needs to be solved. In order to be able to achieve a life balance with the principles of The Purpose Venn Diagram and to have a personality with values of integrity, professionalism, entrepreneurship, and creativity, this study designed an interactive card game design as a communication medium for sharing stories with peers. A qualitative approach utilizing the design thinking method has been implemented to observe the psychological shifts in students following the use of this game card. According to the study findings, this playing card has the potential to serve as both a communication facilitator and an engaging form of entertainment for college students.